Environmental certifications and programs roadmap for a sustainable chemical industry. Issue 3 (21st January 2019) - Swarr, T. E.; Cucciniello, R.; Cespi, D.
Abstract : Benign chemistry will require companies to develop holistic approaches that manage chemicals from three different perspectives that focus on chemicals, products and the organization. Abstract : Meeting public demands for benign chemistry will require companies to develop holistic approaches that manage chemicals from three different perspectives that focus on the organization, its products, or specific chemical materials. A more collaborative approach to chemical management will depend on building trust among a diverse group of stakeholders with often conflicting objectives.